PERSEPSI DAN PRAKTIK ASI EKSKLUSIF OLEH IBU PEKERJA DI FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA - , FAJRI FITRIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The lack of motivation and misconception among working mothers who give breastfeeding has been identified as one of the reason which makes a failed attempt in the breastfeeding practice. One of the strategy the government has anticipated regarding the support to this campaign is through Government Regulation No 33/2012. As a medical institution, a studies research regarding breastfeeding practice by working mother in the Faculty of Medicine Gadjah Mada University (FM UGM) had never been done before. Goal: To identify the perception from working mother in and to describe the practice of breastfeeding in FM UGM. Method: This research is a qualitative-based research which surveyed 17 staff in FM UGM. The subject are women who is doing breastfeed or having a two years or less child at the moment. Triangulation is done by in-depth interview to six heads staff of FM UGM and four woman staff, also through documentation study. Results: Exclusive breastfeeding is significant in the process of babies growth. The research shows eleven informants still carries on the breastfeeding activity in the workplace. They done many alternatives effort